2022
DOI: 10.1002/mrc.5266
|View full text |Cite
|
Sign up to set email alerts
|

A supramolecular and liquid crystalline water‐based alignment medium based on azobenzene‐substituted 1,3,5‐benzenetricarboxamides

Abstract: A supramolecular, lyotropic liquid crystalline alignment medium based on an azobenzene‐containing 1,3,5‐benzenetricarboxamide (BTA) building block is described and investigated. As we demonstrate, this water‐based system is suitable for the investigation of various water‐soluble analytes and allows for a scaling of alignment strength through variation of temperature. Additionally, alignment is shown to reversibly collapse above a certain temperature, yielding an isotropic solution. This collapse allows for iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The isotropic 1 J CH values found in the relaxed gel are in good agreement with those observed by Silva et al [7] but some notable differences can be found with those reported by Venable [31] and Knoll. [9] (See Table S1 in the Supporting Information)…”
Section: Sucrose (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The isotropic 1 J CH values found in the relaxed gel are in good agreement with those observed by Silva et al [7] but some notable differences can be found with those reported by Venable [31] and Knoll. [9] (See Table S1 in the Supporting Information)…”
Section: Sucrose (1)mentioning
confidence: 99%
“…Many of the early reports of application of Residual Dipolar Couplings (RDCs) to the structural analysis of organic molecules were performed in aqueous solution due to the availability of many lyotropic liquid crystal (LLC) weakly-aligning media known to work for biopolymers. [1][2][3][4] Other water-compatible LLC systems, more recently studied or developed by our and other groups, involve chromonic systems, [5][6][7] as well as grapheneoxide, [8] 1,3,5-benzenetricarboxamide (BTA), [9] and nanodiscs. [10][11][12] Among the other big family of NMR weaklyaligning media, the polymer gels, we can find also watercompatible media such as the universal poly(ethylene glycol) gel introduced by Luy and coworkers, the copolymeric gels developed in Griesinger and Gil groups, [13][14][15] or gelatin-based gels.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the photoswitching properties of azo materials, a large number of research groups have worked on to synthesized azo based various shaped liquid crystalline materials with good photophysical properties [19–25] . In the literature survey, very few reports published on supramolecular materials based on azo linker bearing columnar liquid crystalline properties [26–28] . Calixarene is a well‐known macrocycle having significant active blocks with well‐organized molecular shape which make them more specific towards the host‐guest recognition properties [29] .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] In the literature survey, very few reports published on supramolecular materials based on azo linker bearing columnar liquid crystalline properties. [26][27][28] Calixarene is a well-known macrocycle having significant active blocks with well-organized molecular shape which make them more specific towards the host-guest recognition properties. [29] It has a polar rim, a nonpolar rim and a hydrophobic cavity which can be functionalized by different moieties and groups.…”
Section: Introductionmentioning
confidence: 99%